Aspectos processuais da recuperação judicial - Barros Neto, Geraldo Fonseca de (2012)
The objective of this dissertation is to analyse the judicial reorganization, conceived from the civil procedure law perspective. This proposed perspective is justified by the finding that reorganization can only take place through procedure law. The richness of the specialty of the proceedings related to reorganization decurrent from the complexity and specificity of the substantive law in scene makes this study even more relevant. In fact, intricate questions arise out of the practical concretion of reorganization, whose solution is found in the light of civil procedure law. Therefore, proceedings shall be studied in connection with the substantive law to which it has been drawn, as procedure law shall not be conceived as an end in itself. Baring this premise in mind, this paper firstly analyses the jurisdictional structure of restructuring, focusing on competence, the judicial trustee and the participation of the Public Prosecution Office. Subsequently, the study concentrates on the identification of the parties, specially regarding their legitimacy. Then the requirements for reorganization admission will be tackled in parallel with issues related to the merits. Thereupon, the present dissertation addresses the reorganization proceedings, step by step, from the statement of claim to the final judicial pronouncement which either grants reorganization or, dismissing debtor's plea, decrees the bankruptcy of the debtor. Furthermore, this paper examines the special proceedings applicable to minor business companies, as well as the credits verification and the proceedings emerging from the performance or the non-performance of the approved reorganization plan. Hence, this dissertation embraces the features concerning the practical concretion of companies' reorganization, through the analysis of the unique reorganization proceedings